Parentification, Developpement Et Bien-Etre Du Sujet - NSAIRUN Léonard Yuyun; ZOBO ONONO Zachée; MELOUNOU OBAM Françoise (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2025)
The study on parentification, development and well-being of the subject is based on the research hypothesis that there is a high risk of parentification within any dysfunctional family and that the markers or indices of parentification observed in such families have both positive and negative repercussions on the overall well-being and on the mental, physical, behavioral and relational or social states of the individual. Our main objective is to take a systemic approach to the functioning and dynamics of pathological families. To understand the repercussions of parentification on development, Eric Erickson's psychosocial approach with its notions of crises and developmental trajectories and Bowlby's attachment theory, which distinguishes secure attachment from insecure attachment, served as a supporting framework. On the other hand, we used indicators of positive and negative subjective well-being to understand the psychosocial experience of the parentified subject. The data for this study were collected in the South Cameroon region from four participants based on an interview guide. Based on thematic analyses, the results show that parentification, whether it occurs in childhood, adolescence, adulthood, within the couple or even as a legacy, as is the case with Désiré, is primarily negative because it not only anticipates maturity or biopsychosocial hypermaturity, it distorts the quality of attachment, relationship, interaction and exposes the subject to vulnerability. However, parentification also has positive indices not only in family functioning, but also for the subject, especially when the subject is encouraged in his family system. This promotes a strong capacity to adapt to threatening situations.